FURTHER STUDIES ON THE GROWTH AND YIELD PER RECRUIT OF NEMIPTERUS JAPONICUS (BLOCH) FROM THE TRAWLING GROUNDS OFF KAKINADA - Murty, V Sriramachandra (Indian Journal of Fisheries, 2011)
Oil (lie basis of data on N. japolliclIs from trawl landings at Kakinada, thevon BertalanfIy parameters of growth in length are estimated as L"", = 339 mm,K = 0.52 per year and 1>0 = -0.16 year. The mortality rates are estimated asZ = 2.64, M ~, 1.11 and F '" 1.53. The length at first capture is estimated as120 mm. The yield per recruit analysis shows that increase in effort from the presentlevel results in reduced yield from the present fishing ground if the cod endmesh size is not increased.